Pemanfaatan Office 365 Dan Teknologi Cloud Bagi Guru TK ABA Kadipolo di Masa Pandemi Covid-19 - Ainul Yaqin; Alfriadi Dwi Atmoko (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2022)
This community service activity was carried out to provide assistance to TK ABA Kadipolo teachers, this is regarding changes in academic activity models due to conditions were caused by the Covid-19 pandemic. The implementation of community service activities is carried out in 3 stages, starting from pre-activities, then continued with activities carried out in the form of online and offline training related to the use of office 365 and Cloud Computing Technology. As well as the evaluation stage which is carried out by obtaining feedback testimonials from participants. The material in training activities using office 365 online by accessing the office.com page and cloud computing technology as a storage used in training is One Drive. In general, community service activity funded by LPM Universitas AMIKOM Yogyakarta in the 2020 on TDPT program was carried out well and provided new insights for participants about the application of cloud computing technology.